Parents Role in Learning of Elementary Students During The Covid-19 Pandemic - Alfina Tri Buanawati; Risma Rahmawati; Zaiful Hidayat; Ratna Hidayah; Cucuk Budiyanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
A mid of the Covid-19 pandemic, our education should be continued. Therefore, the online learning was being implemented at home so the parents would have a role to make the learning continues. This article aims to analyze parents role in elementary students learning process during the Covid-19 pandemic. The research method is a qualitative approach with descriptive methods. Data obtained from a questionnaire consisting of 17 statements. The population in this study were parents of elementary school students who were affected by the Covid-19 pandemic as many as 60 respondents. The results of this study are the percentage of parents role in elementary school student learning during the Covid-19 pandemic. The conclusion of this article is that parents play a good role in elementary school student learning in the Covid-19 pandemic is as teachers, facilitators, motivators, and influencer. This article can be used as literature and other researchers development material.